2007
DOI: 10.1248/jhs.53.750
|View full text |Cite
|
Sign up to set email alerts
|

A Plasmidic Class 1 Integron from Five Pseudomonas aeruginosa Clinical Strains Harbored aacA4 and Nonsense-mutated cmlA1 Gene Cassettes

Abstract: Five strains of multidrug-resistant Pseudomonas aeruginosa (P. aeruginosa) were isolated from inpatients at a local hospital in China. The most frequent resistance was to cefoperazone, ciprofloxacin, ceftriaxone, cefotaxime, gentamicin, piperacillin, trimethoprim sulfamethoxazole, and tobramycin. These strains were found to contain the class 1 integron, in which the 2360-bp gene cassettes were flanked by 5 -and 3 -conserved segments. Sequence analysis revealed that the gene cassettes contained aacA4 and cmlA1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Yan et al conducted another study on the presence of integron genes in 118 bacterial strains including both Gram-positive and -negative ones; moreover, they assessed antibiotic resistances among these strains and the association between the presence of resistant genes and antibiotic resistance (20). The results of their study demonstrated that 100 out of 118 strains (84.7%) were resistant to more than 3 antibiotics, and then, categorized as multidrug re- (16) sistance.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al conducted another study on the presence of integron genes in 118 bacterial strains including both Gram-positive and -negative ones; moreover, they assessed antibiotic resistances among these strains and the association between the presence of resistant genes and antibiotic resistance (20). The results of their study demonstrated that 100 out of 118 strains (84.7%) were resistant to more than 3 antibiotics, and then, categorized as multidrug re- (16) sistance.…”
Section: Discussionmentioning
confidence: 99%
“…While 5' conserved region of class 1 integron includes class 1 integrase gene encoding a site-specific integrase (intI) and recombination site, 3' conserved region includes sulI and qacEΔ1 genes [18]. Class 1 integrons have been reported in P. aeruginosa isolates [8,[19][20][21][22][23][24][25][26][27]. Organization of class 2 integrons is similar to the class 1 integrons and they are inserted in the Tn7 transposons family.…”
Section: Introductionmentioning
confidence: 99%